Myocardial ischemic preconditioning in a porcine model leads to rapid changes in cardiac extracellular vesicle messenger RNA content. (1st September 2015) - Svennerholm, Kristina; Rodsand, Pouria; Hellman, Urban; Lundholm, Marie; Waldenström, Anders; Biber, Björn; Ronquist, Gunnar; Haney, Michael
Abstract: Background: Extracellular vesicles (EVs) are thought to exert protective effects after ischemic and remote ischemic preconditioning. It is not well understood which EV content factors are most relevant for protective effects. We hypothesize that ischemic preconditioning leads to qualitative changes in EV mRNA content and quantitative changes in EV size and number. Methods: Using an in vivo porcine ischemic preconditioning model, EVs were collected from coronary venous blood, and isolated by differential ultracentrifugations. The presence and purity of EV were verified by electron microscopy and Western blot, and EV number was assessed by nanoparticle tracking analysis. The mRNA EV was identified by microarray. Results: Gene ontology analysis showed enrichment of EV mRNA coding for proteins associated with regulation of transcription, translation, extracellular matrix, morphogenic development and feeding behavior. There were 11, 678 different mRNA transcripts detected in EV, where a total of 1103 was significantly increased or decreased after preconditioning, of which 638 mRNA sequences were up-regulated and/or emerged due to preconditioning. Several of them have known association with ischemic preconditioning. There was no significant difference in EV quantity or size before and after preconditioning. Conclusions: These findings demonstrate in an in vivo model that myocardial ischemic preconditioning influences the composition of mRNA in EV, including gene transcripts for proteins associated with the protective effect of ischemic preconditioning. The finding that preconditioned parental cells release EV containing mRNA that is qualitatively different from those released by non-preconditioned cells shows the importance of the external milieu on parental cell EV production.